ARIH2 serves as a potential prognostic biomarker for hepatocellular carcinoma associated with immune infiltration and ferroptosis - Shu, Qiang; Wang, Qiang; Yang, Xiaoli; Li, Bo (Frontiers in Immunology, 2025)
BackgroundAriadne homolog 2 (ARIH2) has been demonstrated to be upregulated in various human cancer tissues. Nevertheless, the underlying biological function of ARIH2 in the progression of hepatocellular carcinoma (HCC) remains ambiguous. Hence, we conducted a comprehensive bioinformatics analysis on the liver hepatocellular carcinoma (LIHC) dataset to explore the role of ARIH2 in tumorigenesis.MethodsThe mRNA and protein expression of ARIH2 was analyzed by using data from public databases and verified through immunohistochemical staining and Western blot. Logistic regression, Cox regression, receiver operating characteristic curve (ROC), Kaplan-Meier analysis and nomogram model were employed to assess the association between ARIH2 and the clinicopathological characteristics of HCC. We utilized functional enrichment analysis to investigate the potential pathways of ARIH2 in the progression of HCC. The association of ARIH2 with immune infiltration, ferroptosis and immune checkpoint genes was further evaluated. Finally, the correlation between ARIH2 and the IC50 of chemotherapeutic drugs was analyzed in HCC.ResultsOur study discovered that ARIH2 was up-regulated in HCC tumor tissues compared with the control group. ARIH2 expression could effectively distinguish tumor tissues from normal liver tissues. The genes related to ARIH2 showed differential expression in pathways involving immune system-related pathways and ion channels. We identified a significant association between the expression level of ARIH2 in HCC tissues and immune infiltration, immune checkpoint genes and ferroptosis. The expression level of ARIH2 was significantly correlated with the clinical stage, histological pathological grade and clinical characteristics of HCC, and could independently predict overall survival.ConclusionsThe expression level of ARIH2 may serve as a promising biomarker for the diagnosis and prognosis of HCC, as well as a potential drug target, which holds great significance for the development of targeted therapy for HCC.